FIRST RECORD OF Dianema urostriatum (Miranda Ribeiro 1912) (SILURIFORMES: CALLYCHTHIDAE), IN THE PUTUMAYO RIVER, AMAZON BASIN, PERU - RUIZ-TAFUR, Morgan (2022)
The presence of Dianema urostriatum (Miranda Ribeiro, 1912), is formally reported in tributaries of the Putumayo River, Perú, expanding its geographic distribution of the Amazon basin. This record enriches the Peruvian continental ichthyofauna.